Effect of hyperbranched poly(trimellitic glyceride) with different molecular weight on starch plasticization and compatibility with polyester. (1st September 2018) - Zhang, Kang; Cheng, Fei; Lin, Yi; Zhou, Mi; Zhu, Pu-xin
Graphical abstract: Highlights: Hyperbranched polyesters (PTGs) with different molecular weight were synthesized. PTGs with different molecular weight were used to plasticize maize starch (S). PTGs/S had better mechanical property and thermal stability than glycerol/starch. PTGs/S had lower moisture absorption than glycerol/starch (GLY/S). PTGs/S had better effect on adhesion to cotton and polyester yarns than GLY/S. Abstract: Hyperbranched poly(trimellitic glyceride) (PTG) plasticizers for starch were prepared by using trimellitic anhydride and glycerol as raw materials in a simple one-step synthesis. The structure and branching degree of PTGs were confirmed by Fourier transformed infrared, gel permeation chromatography and 1 H nuclear magnetic resonance. The PTGs as plasticizers were composited with maize starch (S) via cooking and film formation. The structure and mechanical, thermal properties of the plasticized starch composites, and its adhesion to cotton and polyester yarns were studied in details. Results indicated that the PTG/S composites had better mechanical property and thermal stability, and lower moisture absorption than glycerol/starch (GLY/S) with the same content (w/w). With the increase in PTG molecular weight, elongation at break of PTG/S film decreased and tensile strength increased, and moisture absorption of PTGs/S reduced. In addition, PTGs/S had a better effect on adhesion to cotton and polyester yarns than GLY/S.